Intra-Regional Inequalities and Poverty Reduction in the Chorotega Region - Sauma, Pablo (2011)
The Chorotega region witnessed a notable reduction in its poverty incidence —measured using income— between 1994 and 2009. Even so, this region’s povertyincidence remains among the highest in the country. The use of various indicatorsof development and poverty, as well as some of the region’s own characteristics,enables verification that such high levels of poverty are explained by economic, social,geographical, and other inequalities within the region. Policy recommendations aremade aiming at reducing poverty in the region